2018
DOI: 10.1152/japplphysiol.00963.2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recurrent laryngeal nerve lesion on oropharyngeal muscle activity and sensorimotor integration in an infant pig model

Abstract: The successful performance of a swallow requires dynamic integration between a wide range of sensory inputs and muscle activities to produce the coordinated kinematics of oropharyngeal structures. Damage to the recurrent laryngeal nerve (RLN) produces dysphagia in infants, with food or liquid entering the airway despite this nerve having minimal direct sensory or motor connections to the act of swallowing, apart from vocal fold closure. Previous results have demonstrated that a complete RLN lesion disrupts bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…R. Soc. B 288: 20210052 sides, as previous work examining muscle firing patterns has demonstrated (electronic supplementary material, figure S1) [34].…”
Section: (D) Data Processingsupporting
confidence: 52%
“…R. Soc. B 288: 20210052 sides, as previous work examining muscle firing patterns has demonstrated (electronic supplementary material, figure S1) [34].…”
Section: (D) Data Processingsupporting
confidence: 52%
“…Because these changes are related to airway protection outcomes, it seems more likely that the mechanism of aspiration is related to kinematics and bolus formation early in the swallow. Indeed, work on the effects of RLN lesion on patterns of muscle activation, both duration and timing, in swallowing has shown changes in the timing of muscle contraction for muscles located in the floor of the mouth, and which are active early in the swallow sequence before bolus formation (30). However, a complete comparison requires similar data for the SLN lesion animals.…”
Section: Despite Both Resulting In Increased Aspiration Rln and Sln mentioning
confidence: 99%
“…Theoretically, individuals with isolated injury to the RLN are capable of achieving airway safety due to the compensatory contributions of the supraglottic larynx, the unimpaired side of the larynx, normal hyolaryngeal excursion, and pharyngeal constriction and shortening . Support for this compensation theory was found in a piglet model in which dynamic reorganization of the pharyngeal swallow and adequate airway protection were demonstrated subsequent to isolated RLN damage . In addition, Dworkin and Treadway found that 70% of a retrospective cohort of adults diagnosed with idiopathic UVP (N = 30) did not report any form of dysphagia .…”
Section: Discussionmentioning
confidence: 99%